Evaluation of the Economic Efficiency of Heat Recovery from Exhaust Gas of Diesel Power Plants in Kazakhstan - Orynkanova, Zhanar M.; Stepanova, Diana I. (International Journal of Energy Economics and Policy, 2020)
In today’s world, the issue of efficient energy consumption and reducing dependence on fossil energy resources is especially acute. Each extra kilowatt-hour of electricity is a significant burden on the expenses of any type of enterprise, leading to a decrease in its competitiveness. The first step in solving this problem should be a general reduction in energy consumption by increasing the energy efficiency of the equipment used, choosing the best solutions for engineering systems and implementing a range of energy-saving measures. This study presents an instrument for achieving energy efficiency by utilizing waste gas heat on the example of existing fixed assets of diesel power plants in Kazakhstan. Based on an analysis of the technical indicators of the equipment, an economic analysis of the feasibility of utilizing the internal combustion engine’s (ICE) waste heat is carried out. With the help of the latter it is determined that in the conditions of market electricity tariffs in Kazakhstan, the indicated innovations can be implemented in 3-3.5 years. Keywords: energy efficiency, heat recovery, economic efficiency, secondary energy management. JEL Classifications: Q40; Q42; Q47 DOI: https://doi.org/10.32479/ijeep.9360